2020
DOI: 10.1088/2053-1591/ab8e70
|View full text |Cite
|
Sign up to set email alerts
|

Research of selective etching in LiNbO3 using proton-exchanged wet etching technique

Abstract: Lithium niobate material (LN) has shown great application potentials in the fabrication of integrated optical devices due to its excellent physical properties, especially with the occurrence of lithium niobate-on-insulator (LNOI) substrate. However, the greatest challenge of micro/nano optical devices based on LN material lies in the precise etching process and thus limits its applications. In this paper, we comprehensively analyze the etching results treated by the proposed proton-exchanged wet-etching method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…199 Therefore, the combination of PE and a mixture of HF and HNO 3 etchant is widely used for LN wet etching. 109,[199][200][201][202][203][204] Compared with dry etching, its etched sidewall is not too deep and there can be an underetching problem. Ting et al demonstrated that the etching depth and aspect ratio can be improved using a diluted PE source with a lithium compound.…”
Section: Wet Etchingmentioning
confidence: 99%
“…199 Therefore, the combination of PE and a mixture of HF and HNO 3 etchant is widely used for LN wet etching. 109,[199][200][201][202][203][204] Compared with dry etching, its etched sidewall is not too deep and there can be an underetching problem. Ting et al demonstrated that the etching depth and aspect ratio can be improved using a diluted PE source with a lithium compound.…”
Section: Wet Etchingmentioning
confidence: 99%
“…Previous studies have shown an improved etching rate in the inverted LN ferroelectric domains. [20][21][22][23] Based on domain engineering techniques such as electrical field poling, 20,21 ionbeam irradiation, 24,25 and laser poling, 22,26,27 the highest etching rate in x-cut LN is reported to be ∼80 nm h −1 by using 40% HF solution. 22 Currently, it is still a great challenge to selectively enhance the etching rate to several microns per hour for LN nanofabrication with a large aspect ratio and high in-plane precision.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the nanofabrication of the memory cells remains a significant challenge, particularly in terms of LNO etching. Generally, acoustic and optical LNO microdevices can be fabricated through wet chemical etching processes using HF/HNO 3 mixed solution and SC-1 solution (NH 4 OH/H 2 O 2 /H 2 O). However, the wet etching processes are isotropic and hence cannot transfer the fidelity of etched patterns at the nanometer-sized scale. Therefore, much effort has been dedicated to improve dry etching processes due to their advantages of anisotropic etching, precisely controlled etching patterns, faster processing, and compatibility with materials unsuitable for wet etching. , …”
Section: Introductionmentioning
confidence: 99%